2021
DOI: 10.3390/w13111509
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Extreme Precipitation in Four Climate Regions in China by General Circulation Models (GCMs): Performance and Projections

Abstract: In the context of global climate change, it is important to monitor abnormal changes in extreme precipitation events that lead to frequent floods. This research used precipitation indices to describe variations in extreme precipitation and analyzed the characteristics of extreme precipitation in four climatic (arid, semi-arid, semi-humid and humid) regions across China. The equidistant cumulative distribution function (EDCDF) method was used to downscale and bias-correct daily precipitation in eight Coupled Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 46 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…The uncertainties related to climate change impact assessment include the future emission scenarios, climate models, and downscaling methods used. This study showed that the NORESM1-M mode using the RCP4.5 and RCP8.5 scenarios can be applied well in a region of China (Zhang et al 2021). However, there are some other uncertainties that arise when only one climate model is used for such a purpose.…”
Section: Discussionmentioning
confidence: 88%
“…The uncertainties related to climate change impact assessment include the future emission scenarios, climate models, and downscaling methods used. This study showed that the NORESM1-M mode using the RCP4.5 and RCP8.5 scenarios can be applied well in a region of China (Zhang et al 2021). However, there are some other uncertainties that arise when only one climate model is used for such a purpose.…”
Section: Discussionmentioning
confidence: 88%
“…With an increase in rainfall intensity, rainfall erosivity is enhanced [23]. Many studies have reported that extreme precipitation events have occurred more frequently and with increasing intensity in recent decades [24,25]. We can infer that with the further increase in extreme precipitation events in the future, the frequency and amount of surface runoff in tea plantations will increase.…”
Section: Plos Onementioning
confidence: 93%
“…Few studies have explored the causes of extreme precipitation from the perspective of land surface processes or thermal anomalies, and there are still many uncertainties in the understanding of land-atmosphere interactions in arid regions. The changes in landatmosphere coupling and coupling mechanisms are very important for accurately predicting future climate (Chen and Zhou 2013;Diro et al, 2014;Zscheischler et al, 2015;Chen et al, 2017;Zhang et al, 2021). The existing method for comprehending and enhancing the Earth-atmosphere system and its variability in climate change prediction continues to have weaknesses in understanding land-atmosphere interactions (Santanello et al, 2015).…”
Section: Introductionmentioning
confidence: 99%